Psychosocial decision making factors in military: a pilot study - Ambrulaitienė, Giedrė (Social Welfare: Interdisciplinary Approach, 2017)
It can be said that one of the main fundamentals of life welfare is right decision-making. There are no doubts that we would get two different outcomes after choosing right or wrong decisions in decisive moments of life. This takes into account any sphere of life. Speaking about military platform we see that sometimes decisions even in tactical level can make huge impact to strategic levels and this can directly affect life welfare of whole country or even regions. So, right decisions in military are important not only to the welfare of soldiers, but can be also important to peaceful survival of the humanity in various places of the world, speaking in general way. The analysis of scientific literature revealed that during military decision making process officers usually face large number of decision-making factors. Literature analysis revealed three most important factor groups in the military decision making process: psychological, social and situational. The aim of this article is to compare social (Rank, Time of service, Marital status) and psychological (Self – efficacy in General; Self – efficacy in TLP) factors in military tasks. Situational factors will not be part of this study. The main situational factors were included in each military decision making tasks. Research results disclosed, that higher self-efficacy in general appears when main goal of military task is maintenance of LT statehood and sovereignty and given specific military task is mainly blocking. Lower self-efficacy in general appears when main goals are safety of important specific objects that would damage states’ specific spheres like energy, transportation or economy and specific military tasks are disrupting and disturbing. Officers with higher self-efficacy in TLP more often choose successful decisions in nine different specific military tasks. Officers’ higher self-efficacy in TLP is more important to successful decision making than officers’ higher self-efficacy in general.